From individual motivations to social determinants: towards a sociology of migrants’ remittances - Hasan Mahmud (241078) (2020)
Migrants may send remittances for a variety of reasons. Studies adopting the perspective of the new economics of labour migration (NEML) identify migrants’ altruism or self-interest as the motivation for their remittances. This paper first recognises the limits of the NELM perspective due to its utilitarian conception of migrants’ altruism and inability to distinguish between altruism and self-interest. The discussion also reveals a preponderance of quantitative studies examining remittance utilisation in the origin communities in the absence of the migrants who are sending the funds. These studies must necessarily indirectly deduce migrants’ motivation to send remittances, leading to post hoc and inconsistent interpretations. In a review of the existing literature, this paper identifies alternative conceptualisations of migrants’ agency and structures embedding their remittances as well as emergent properties of both their agency and those structures. Lastly, it outlines a heuristic typology to empirically study migrants’ remittances following Durkheim's approach to suicide, demonstrating the usefulness of this typology by citing examples from the literature as well as reflecting the author's dissertation research. Other Information Published in: International Social Science Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/issj.12247